Analysis of Factors Associated with Blood Pressure in Patients with Uncontrolled Hypertension at Health Center I West Denpasar - I Gusti Ayu Ari Rasdini; I Dewa Putu Gede Putra Yasa; Ni Made Wedri; I Wayan Sukawana; Lina Adhiutami (KHD-Production, 2023)
Hypertension is a non-communicable disease which is currently a major challenge for global and national community healing, and is one of the most common causes of death in the world. According to the NHANES, blood pressure that is not normalized is defined as systolic blood pressure ≥ 140 mmHg or diastolic blood pressure ≥ 90 mmHg, where the patient is unconscious, conscious but not treated or treated with antihypertensive drugs. Factors that can cause uncontrolled blood pressure are uncontrollable and controllable factors, namely salt consumption, coffee consumption, and obesity. Analyzing the factors associated with blood pressure in patients with uncontrolled hypertension at Health Center I West Denpasar. This study used a cross-sectional analytic survey approach, involving 57 people using the accidental sampling method. Statistical analysis using Chi-square. The results of the chi square analysis showed that the salt consumption factor was p=0.000, the coffee consumption factor was p=0.041, and the obesity factor was p=0.022. The factor that is most closely related to the increase in blood pressure is coffee consumption with an OR value of 0.224 times. Health workers need to provide information about DASH (Dietary Approaches To Stop Hypertension) in hypertensive patients to help reduce increased blood pressure in addition to taking antihypertensive drugs regularly.